Ethnic differences in vascular function and factors contributing to blood pressure - Foulds, Heather J. A. (Can J Public Health, 2018)
OBJECTIVE: Indigenous populations experience greater proportions of cardiovascular disease, diabetes, and obesity, though lower rates of hypertension. This investigation evaluated blood pressure relationships with vascular measures, anthropometry, cultural identity, and smoking status among Canadian Indigenous and European adults. METHODS: In 2013, in Vancouver, Canada, blood pressure, anthropometry, cultural identity, smoking status, pulse wave velocity (PWV), arterial compliance, baroreceptor sensitivity, and intima-media thickness (IMT) were directly measured among 58 Indigenous (39 ± 18 years, 31 female) and 58 age- and sex-matched European Canadian (42 ± 18 years) adults. Systolic (SBP) and diastolic (DBP) blood pressures were related to vascular measures, and hypertension was related to anthropometry, cultural identity, and smoking status. RESULTS: Similar vascular measures were recorded between Indigenous and European adults, respectively (PWV 5.3 ± 2.4 vs. 6.2 ± 3.4 m s(−1), p = 0.12; IMT 0.59 ± 0.11 vs. 0.61 ± 0.11 mm, p = 0.40; and large arterial compliance 16.1 ± 6.4 vs. 17.5 ± 6.6 mL mmHg(−1) × 10, p = 0.26). Similar relationships between vascular measures with SBP and DBP were identified between Indigenous and European adults (spectral baroreceptor sensitivity and SBP, r = 0.48, p = 0.001 vs. r = − 0.11, p = 0.44; ethnic difference p = 0.38; PWV; and DBP, r = 0.23, p = 0.09 vs. r = 0.06, p = 0.65, ethnic difference p = 0.23). Anthropometry only related to blood pressures among Europeans. Cultural identity only related to blood pressures among Indigenous populations. Smoking was not related to hypertension. CONCLUSION: Similar vascular measures between Indigenous and European Canadians were identified among populations experiencing similar social determinants of health.